Expression of p53 as a biomarker of pazopanib efficacy in solitary fibrous tumours: translational analysis of a phase II trial. (August 2022) - Napolitano, Andrea; Moura, David S.; Hindi, Nadia; Mondaza-Hernandez, José L; Merino-Garcia, José A.; Ramos, Rafael; Dagrada, Gian Paolo; Stacchiotti, Silvia; Graziano, Francesco; Vincenzi, Bruno; Martin-Broto, Javier
Background: Solitary fibrous tumours (SFT) are soft tissue sarcomas molecularly defined by the presence of the NAB2::STAT6 intrachromosomal fusion gene. Recently, a prospective phase II trial evaluating the role of the antiangiogenic tyrosine kinase inhibitor pazopanib in SFT has been conducted (NCT02066285). Methods: Here, we analysed the mRNA and protein expression levels of the tumour suppressor and angiogenesis regulator p53 ( TP53 ) in pre-treatment tumour samples from 22 patients with low aggressive (or typical) SFT and 28 patients with high aggressive (26 malignant and 2 dedifferentiated) SFT enrolled in the aforementioned pazopanib phase II trial. These results were correlated with radiological progression-free survival (PFS) and objective response. Univariate and multivariate Cox regression analyses were also performed, including known clinic-pathological prognostic factors. Results: Diffuse immunohistochemistry (IHC) expression of p53 was only found in patients with aggressive SFT and was associated with significantly shorter PFS [hazard ratio (HR): 4.39, 95% confidence interval (CI): 1.19–16.14). TP53 mRNA levels were significantly higher in the low aggressive SFT group. Only in the high aggressive SFT group, relatively higher levels of TP53 were significantly associated with shorter PFS (HR: 4.16, 95% CI: 1.46–11.89) as well as to a lower rate of disease control following treatment with pazopanib. In the multivariate analysis, the only independent prognostic factor in the whole cohort was mitotic count. Conclusion: Diffuse p53 IHC expression and higher TP53 mRNA levels are associated with worse prognosis in the subset of aggressive SFT patients treated with pazopanib.